Retrospect and Prospect on Regional Industrial Policy in South Korea: The Case of Gwangju-Chonnam Region - Lee, Sang-Ho; Kim, Seung-Leul (Journal of Development and Administrative Studies, 2015)
Gwangju-Chonnam region has long been recognized as an economically hollow region of South Korea. Even though there have been various kinds of policies and investments to vitalize its economy not only from central government, but also from local governments, its relative position in the country is not much changed. This paper is devoted to examine the industrial structure enhancement policies in Gwangju-Chonnam region in South Korea. First, we review the history of regional industrial policy implemented in Gwangju-Chonnam region, and present some policy considerations on regional economic innovation. Second, we classify regional policy directives by historical period, describe policy contents of each period, and discuss the limitations of regional policies adopted by the local governments, after pointing out important factors in selecting regional specialized industry by regions. Finally, under the economic environment faced with global trend of open competition, a brief policy recommendation is suggested in the conclusion. The Journal of Development and Administrative Studies, Vol. 22, No. 1-2, pp. 51-66, 2014